Hypotension associated to a bilateral quadratus lumborum block performed for post-operative analgesia in an open aortic surgery case - Almeida,Carlos (2018)
Abstract Background and objectives: Bilateral quadratus lumborum block has been described for major abdominal procedures when sepsis is present, because risks associated to epidural are considered elevated. In an open aortic surgery, a single-shot bilateral quadratus lumborum block type 1 may be an alternative to thoracic epidural block for post-operative analgesia in a patient having an increased cumulative risk for thoracic epidural hematoma. Case report: A 56-year-old female patient presenting controlled hypertension, chronic renal disease stage 3b, dyslipidemia and a platelet count of 102,000/µl, and taking aspirin, was scheduled for bilateral aortoiliac endarterectomy. She was submitted to a sole general anesthesia plus, at end of the surgery, a bilateral quadratus lumborum block type 1 for post-operative analgesia with 20 mL of ropivacaine 0.5%, per side, before extubation. Immediately after post anesthesia care unit admission, patient developed moderate hypotension (dopamine infusion was needed during 18 h), concomitantly with a rapid reduction in the pain scores. Low numeric rating scale and opioid consumption were noted, particularly in the first 24 h post-operatively. Conclusions: Quadratus lumborum block was an effective analgesic technique for open aortic surgery in this case, although hypotension associated to bilateral quadratus lumborum block type 1 may occur. Associated sympathetic block probably related to the bilateral paravertebral extension of the block, may contribute for post-operative hypotension associated to reperfusion-ischemia syndrome in a patient that had long-lasting intraoperative aortic cross-clamping. The use of high concentration of local anesthetic to obtain longer duration of action of a single-shot quadratus lumborum block to avoid thoracic epidural or bilateral quadratus lumborum block catheterization should be used judiciously.